Pendekatan Rukun Madani: Daya Cipta Dalam Pengurusan Zakat Institusi Pengajian Tinggi - Muhammad Azhad Al-Bohari; Azman Ab. Rahman (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
International Conference of Postgraduate Students and Academics in Syariah and Law 2025 (INPAC 2025) “Advancing Malaysia Madani through Global Shariah and Legal Research.” Organized by the Faculty of Syariah and Law, Universiti Sains Islam Malaysia (USIM)